2019
DOI: 10.1186/s12883-019-1321-7
|View full text |Cite
|
Sign up to set email alerts
|

Over-ground walking or robot-assisted gait training in people with multiple sclerosis: does the effect depend on baseline walking speed and disease related disabilities? A systematic review and meta-regression

Abstract: Background It was suggested that robot-assisted gait training (RAGT) should not be routinely provided to disabled patients in place of conventional over-ground walking training (CGT). There exist several randomised controlled trials reporting on RAGT for people with multiple sclerosis. However, the effectiveness of RAGT varies between studies with the effectiveness pointing in different directions. It might be possible that the effectiveness of RAGT and CGT depends on the disease related disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
2
26
0
1
Order By: Relevance
“…Sessions included training on elements of stretching, strengthening, ambulation training, balance training, weight support, transfer training, stepping length and width and weight shift during ambulation (see Fig. 2) (Aisen, et al, 1996;Haselkorn, et al, 2015;Sattelmayer, et al, 2019;Sutliff, et al, 2016). Throughout the 4-weeks, CGT progressed in terms of duration (matching that of the REAER condition) and difficulty of training elements (e.g., narrowing base of support, performing activities with eyes closed, etc.).…”
Section: Control Conditionmentioning
confidence: 99%
“…Sessions included training on elements of stretching, strengthening, ambulation training, balance training, weight support, transfer training, stepping length and width and weight shift during ambulation (see Fig. 2) (Aisen, et al, 1996;Haselkorn, et al, 2015;Sattelmayer, et al, 2019;Sutliff, et al, 2016). Throughout the 4-weeks, CGT progressed in terms of duration (matching that of the REAER condition) and difficulty of training elements (e.g., narrowing base of support, performing activities with eyes closed, etc.).…”
Section: Control Conditionmentioning
confidence: 99%
“…Seventeen RCTs (n=810), [94][95][96][97][98][99][100][101][102][103][104]107,108,[110][111][112][114][115][116] one quasiexperimental study (n=44), 105 and one cohort study 106 (n=24) evaluated RAGT interventions. These included eight RAGT studies versus usual care, 95,98,101,102,104,106,112,115,116 one versus no intervention, 114 two RCTs versus overground gait training, 107,108 and eight RCTs versus other interventions such as aquatics, taskoriented physical therapy (TOP), and nonrobotic treadmill training.…”
Section: Detailed Synthesismentioning
confidence: 99%
“…Seventeen RCTs (n=810), [94][95][96][97][98][99][100][101][102][103][104]107,108,[110][111][112][114][115][116] one quasiexperimental study (n=44), 105 and one cohort study 106 (n=24) evaluated RAGT interventions. These included eight RAGT studies versus usual care, 95,98,101,102,104,106,112,115,116 one versus no intervention, 114 two RCTs versus overground gait training, 107,108 and eight RCTs versus other interventions such as aquatics, taskoriented physical therapy (TOP), and nonrobotic treadmill training. Five RCTs enrolled participants with MS (Table 14), seven RCTs enrolled children and adolescents with CP (Table 15), one RCT enrolled adolescents and adults, 104 and the remaining RAGT studies were in adults, and ten RCTs were conducted in participants with SCI (Table 16).…”
Section: Detailed Synthesismentioning
confidence: 99%
“…evaluated in MS (28). RAGT consists on a training modality in which the patient's body weight is supported by a harness while walking on a treadmill with the help of a roboticdriven gait orthosis (29). Morone et al (30) have identified the following characteristics of RAGT devices: i) capable of mobility with different levels of autonomy, ii) could be classified as either "exoskeletons" (when the movement of specific joints is controlled [i.e.…”
Section: Introductionmentioning
confidence: 99%